PENGARUH PENGGUNAAN METODE GIVING QUESTIONS AND GETTING ANSWER TERHADAP BERPIKIR KRITIS DAN KEAKTIFAN SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI SMP NEGERI 2 NGANTRU - Nafi'ur rohman (Universitas Negeri Semarang, 2025)
This research is motivated by the low level of students' activeness and critical thinking skills in social studies learning which is often considered boring and difficult, causing students to become passive. To overcome this, the Giving Questions and Getting Answers (GQGA) method is applied which aims to create a fun, interactive learning atmosphere, and develop students' questioning and answering skills. The purpose of this study was to determine the effect of the GQGA method on students' critical thinking skills and learning activeness in social studies subjects at SMPN 2 Ngantru. This study uses a quantitative approach with the Quasi Experimental type and Nonequivalent Control Group Design. The research sample consisted of 24 control class students and 27 experimental class students selected by purposive sampling. Data were collected using critical thinking tests and student activeness observation sheets, and analyzed using the Independent Sample T-Test and MANOVA. The results showed that the GQGA method had a significant positive effect on students' critical thinking skills and activeness, as indicated by a significance value of 0.000 <0.05. These findings indicate that the GQGA method is effective in improving the quality of social studies learning by making it more interesting and meaningful.